Activation of integrins in endothelial cells by fluid shear stress mediates Rho-dependent cytoskeletal alignment - Tzima, Eleni (Oxford University Press, 2001)
Fluid shear stress is a critical determinant of vascular remodeling and atherogenesis. Both integrins and the small GTPase Rho are implicated in endothelial cell responses to shear but the mechanisms are poorly understood. We now show that shear stress rapidly stimulates conformational activation of integrin αvβ3 in bovine aortic endothelial cells, followed by an increase in its binding to extracellular cell matrix (ECM) proteins. The shear-induced new integrin binding to ECM induces a transient inactivation of Rho similar to that seen when suspended cells are plated on ECM proteins. This transient inhibition is necessary for cytoskeletal alignment in the direction of flow. The results therefore define the role of integrins and Rho in a pathway leading to endothelial cell adaptation to flow.